2012
DOI: 10.1002/dvdy.23773
|View full text |Cite
|
Sign up to set email alerts
|

Airway epithelial cell differentiation during lung organogenesis requires C/EBPα and C/EBPβ

Abstract: Background: CCAAT/enhancer‐binding protein (C/EBP)α is crucial for lung development and differentiation of the pulmonary epithelium. Conversely, no lung defects have been observed in C/EBPβ‐deficient mice, although C/EBPβ trans‐activate pulmonary genes by binding to virtually identical DNA‐sequences as C/EBPα. Thus, the pulmonary phenotype of mice lacking C/EBPβ could be explained by functional replacement with C/EBPα. We investigated whether C/EBPα and C/EBPβ have overlapping functions in regulating lung epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 80 publications
3
37
0
Order By: Relevance
“…Zero, 5, and 20 ng/mL were used, and RNA was collected from the differentiation at day 45. Analysis of lungrelated gene expression at this time point showed that 5 ng/mL supported the most robust up-regulation of genes related to lung development and mature lung cells, such as DE makers FOXA2, GATA6, goblet cell marker MUC5A/C, MUC1, CFTR, and transcription factor cEBPα (important for lung-branching morphogenesis) (33,34), and was thus used as the working concentration for the protocol (shown in SI Appendix, Fig. S7).…”
Section: Resultsmentioning
confidence: 99%
“…Zero, 5, and 20 ng/mL were used, and RNA was collected from the differentiation at day 45. Analysis of lungrelated gene expression at this time point showed that 5 ng/mL supported the most robust up-regulation of genes related to lung development and mature lung cells, such as DE makers FOXA2, GATA6, goblet cell marker MUC5A/C, MUC1, CFTR, and transcription factor cEBPα (important for lung-branching morphogenesis) (33,34), and was thus used as the working concentration for the protocol (shown in SI Appendix, Fig. S7).…”
Section: Resultsmentioning
confidence: 99%
“…1B). A recent report has suggested that CEBPA functions redundantly with CEBPB to promote airway differentiation (Roos et al, 2012). We hypothesize that the airway CEBPA staining we observe reflects a second site of expression and therefore do not use this protein as a specific marker of developing alveolar fate.…”
Section: Resultsmentioning
confidence: 99%
“…IL-17 has been amply implicated in the pathogenesis of asthma 4042 , and studies in dust-mite sensitized subjects have shown that specific immunotherapy can lead to reductions in IL-17 levels that correlate with symptom reduction 43 . However, CEBPβ also participates in several other pathways, including IL-4, IL-6, TNFα and IFN-γ signaling pathways, and it has been implicated in airway epithelium differentiation during lung development 44 . Thus, functional studies will be needed to determine the precise role of CEBPβ in the interaction between dust mite and genotype on lung function in asthma.…”
Section: Discussionmentioning
confidence: 99%